Another new species of Stanhopea (Orchidaceae) from Peru - Jenny, Rudolf (2015)
A new species of Stanhopea (S. naurayi Jenny), recently collected in Peru, is described and illustrated. Not closely allied with any other known species from Peru, it is relatively similar to some forms of the Mexican S. oculata (Lodd.) Lindl. but with flowers one third smaller.